Risk factors for anterior cruciate ligament graft failure in professional athletes: An analysis of 342 patients with a mean follow-up of 100 months from the SANTI study group - Hopper, G. P.; Pioger, C.; Philippe, C.; El Helou, A.; Campos, J. P.; Gousopoulos, L.; Carrozzo, A.; Vieira, T. D.; Sonnery-Cottet, B. (The American Journal of Sports Medicine, 2022)
Background: Anterior cruciate ligament (ACL) injuries are among the most common knee injuries sustained in elite sport, and athletes generally undergo ACL reconstruction (ACLR) to facilitate their return to sport. ACL graft rupture is a career-threatening event for elite athletes.